Suomen intendentinkonttorin kirkkoarkkitehtuuri 1810-1824 : kustavilainen perinne ja suuriruhtinaskunnan uusi rakennushallinto - Kydén, Tarja (1998)
The study examines the church architecture of the Bureau of the Superintendent (intendentinkonttori) of Public Works and Buildings in Finland in 1810-1824, during a period when the agency was led by the ltalian-born Charles Bassi (1772-1840), who had received his training in Sweden. After a war between Sweden and Russia, Finland, previously part of Sweden, was annexed to Russia in 1809; however, before the year was out it received, as a result of the Russian Emperor's pacificatory policies, an autonomous status. The study considers its subject from the perspective of the administration of public building: the new Grand Duchy of Finland was given a central administration and a number of central administrative agencies, one of the first of them being the Bureau of the Superintendent of Public Works and Buildings, created to supervise public construction. The study examined both the legislation governing church architecture, considered part of public construction, on which public building administration was based, and the statements and decisions of the central, intermediate-level and parish administration, representing the level of practical action that influenced the process. A detail analysis was undertaken of the church architecture of the period as a whole without attempting to evaluate individual buildings. The new building administration established in Finland was strongly influenced by laws that had been enacted during the Swedish rule and by concrete practices originating in the same period that were being maintained by the authorities. This was linked with a broader phenomenon that involved an endeavour to emphasize Finland's autonomous status under the Russian great power. Right from the parish level, church-building projects were dominated by economic considerations. In fact, applications for exceptional permits to build timber churches predominated among the petitions submitted in this period to the degree that all parishes came, at least in the final phase of their project, to the decision to apply for a permission to build a timber church instead of a stone one. In determining the design of their new church, parishes paid attention primarily to the choice of church type rather than to stylistic considerations. Provincial governors and the consistories of cathedral chapters played a central role as providers of statements. A good example were applications for timber churches: these authorities' opinions on the desirability of a timber or a stone church were as a rule adopted by the higher administrative organs. The authorities' decision-making was guided by bureaucratic attitudes and a concern to ensure that parishes observed proper official procedures. The official objective was guaranteeing that the parishes would get architecture of a high quality. At the same time it was also a question of the function of churches. Churches' social importance grew in the uncertain situation of the early Age of Autonomy; they were useful for the purposes of the temporal authorities. The decisions of the Economic Department of the Imperial Finnish Senate, the Grand Duchy's highest decision-making body, endorsed in most cases the views of the lower authorities; as a rule it was only when there were conflicting opinions that the Department took a stand on the applications of the parishes. The designs drawn up by the Bureau of the Superintendent were usually approved by the Senate, but when disputes arose the Economic Department favoured conservative and traditional views.